بيع السّلم وتطبيقاته المعاصرة في المصارف الإسلامية في إندونيسيا - AA Hubur (Islamic Economics Journal, 2019)
This research aims to determine the importance of the applications of salam contract on Islamic banking in Indonesia, it focuses on discussing the legality and validity aspects related to salam contract in sharia view. The research also determines in terms of how the contemporary application of salam contract on Islamic banking and the areas of its applications in Indonesia. The research uses descriptive and analytical methods by viewing library resources and personal interviews with experts and employees on Islamic banking in Indonesia. The results of the research concluded that salam contract is in accordance with the demands of financing and is needed to become one of the sharia-based financing products. It concludes that this contract still requires a lot of theoretical and applied studies and research to highlight its financial characteristics and capabilities in economic reality.